The Effect of Ankle Injuries on Marathon Athletes from a Psychological Perspective - Berlian Agatha Silalahi; Ilaika Al Quratu Aini; Fauzi Shaputra Husin; Muhammad Arif Setiawan; Dany Aulia (Gladi : Jurnal Ilmu Keolahragaan, 2026)
This study aims to determine the effect of ankle injury severity on anxiety levels in marathon athletes in Bekasi. The research method uses a quantitative approach with a simple linear regression analysis technique. The study subjects consisted of 75 marathon athletes who had participated in marathon races in Bekasi. The severity of ankle injuries was measured using an injury classification questionnaire that groups injuries into mild, moderate, and severe categories, while the athletes' anxiety levels were measured using a sports anxiety questionnaire instrument that had been adjusted to the athletes' characteristics. The results of the normality test showed that the data were normally distributed (p = 0.065), while the linearity test showed a linear relationship between injury severity and anxiety levels (deviation from linearity p = 0.541). The results of the simple linear regression analysis showed a correlation coefficient (R) of 0.786 and a determination coefficient (R²) of 0.618, which means that 61.8% of the variation in athletes' anxiety levels can be explained by the severity of the ankle injury. The regression equation obtained is Y = 20.315 + 9.215X. The results of the regression test showed that the severity of the ankle injury significantly influenced the athlete's anxiety level (t = 10.829; p = 0.000). This finding indicates that the higher the severity of the injury experienced by the athlete, the higher the level of anxiety felt. Therefore, injury rehabilitation programs for marathon athletes need to integrate physical recovery and psychological support to support optimal recovery processes both physically and mentally.